Sex differences in imaging and clinical characteristics of patients from the WAKE‐UP trial. (23rd November 2022) - Wouters, Anke; Scheldeman, Lauranne; Liessens, Hannelore; Dupont, Patrick; Boutitie, Florent; Cheng, Bastian; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Gerloff, Christian; Muir, Keith W.; Nighoghossian, Norbert; et al.
Abstract: Background and purpose: Sex‐based differences in acute ischemic stroke are a well‐known phenomenon. We aimed to explore these differences between women and men in the Efficacy and Safety of MRI‐Based Thrombolysis in Wake‐Up Stroke (WAKE‐UP) trial. Methods: We compared baseline demographic and imaging characteristics (visual fluid‐attenuated inversion recovery [FLAIR] positivity, relative FLAIR signal intensity, collateral status) between women and men in all screened patients. In randomized patients (i.e., those with diffusion‐weighted imaging (DWI)–FLAIR mismatch), we evaluated a modifying role of sex on the treatment effect of alteplase in multivariable logistic regression, with treatment adjusted for National Institute of Health Stroke Scale (NIHSS) score and age. Dependent variables were modified Rankin Scale (mRS) score of 0–1 at 90 days and distribution of mRS scores at 90 days. Results: Of 1362 screened patients, 529 (38.8%) were women. Women were older than men, had higher baseline NIHSS scores and smoked less frequently. FLAIR positivity of the DWI lesion was equally present in women (174/529, 33.1%) and men (273/833, 33.3%; p = 1.00) and other imaging variables also did not differ between the sexes. In a total of 503 randomized patients, of whom 178 were women (35.4%), sex did not modify the treatment effect of alteplase on mRS score 0–1 or on the total distribution of mRS scores. Conclusion: As in many other stroke trials, more men than women were included in the WAKE‐UP trial, but the presence of a visual DWI–FLAIR mismatch and the relative FLAIR signal intensity did not differ between the sexes. The treatment effect of alteplase was not modified by sex.